Remembering the past in contemporary African American fiction - Byerman, Keith Eldon, 1948- (University of North Carolina Press, 2005)
With readings of more than twenty novels, this book examines the trend among African American novelists of the late twentieth century to write about black history, rather than about their own present. Employing cultural criticism and trauma theory, it frames these works as survivor narratives.